Usability Evaluations of a Wearable Inertial Sensing System and Quality of Movement Metrics for Stroke Survivors by Care Professionals - Klaassen, Bart; van Beijnum, Bert-Jan F.; Held, Jeremia P.; Reenalda, Jasper; van Meulen, Fokke B.; Veltink, Peter H.; Hermens, Hermie J. (Frontiers in Bioengineering and Biotechnology, 2017)
Background Inertial motion capture systems are used in many applications such as measuring the movement quality in stroke survivors. The absence of clinical effectiveness and usability evidence in these assistive technologies into rehabilitation has delayed the transition of research into clinical practice. Recently, a new inertial motion capture system was developed in a project, called INTERACTION, to objectively measure the Quality of Movement (QoM) in stroke survivors during daily-life activity. With INTERACTION, we are to be able to investigate into what happens with patients after discharge from the hospital. Resulting QoM metrics, where a metric is defined as a measure of some property, are subsequently presented to care-professionals. Metrics include for example: reaching distance, walking speed and hand distribution plots. The latter shows a density plot of the hand position in the transversal plane. The objective of this study is to investigate the opinions of care-professionals in using these metrics obtained from INTERACTION and its usability. Methods By means of a semi-structured interview, guided by a presentation showing two patient reports. Each report includes several QoM metric (like reaching distance, hand position density plots, shoulder abduction) results obtained during daily-life measurements and in clinic, and were evaluated by care-professionals not related to the project. The results were compared with care-professionals involved within the INTERACTION project. Furthermore, two questionnaires (5 point Likert and open questionnaire) were handed over to rate the usability of the metrics and to investigate if they would like such a system in their clinic. Results Eleven interviews were conducted, where each interview included either 2 or 3 care-professionals as a group, in Switzerland and the Netherlands. Evaluation of the case-reports by participants and INTERACTION members showed a high correlation for both lower and upper extremity metrics. Participants were most in favour of hand distribution plots during daily-life activities. All participants mentioned that visualising QoM of stroke survivors over time during daily-life activities, has more possibilities compared to current clinical assessments. They also mentioned that these metrics could be important for self-evaluation of stroke survivors. Discussion The results showed that most participants were able understand the metrics presented